Peningkatan Literasi Perubahan Iklim Generasi Muda di Universitas Muhammadiyah Sorong - Syafaati, Ayu Diah; Satria, Budi (Buletin GAW Bariri (BGB), 2025)
Climate change has become a crucial issue affecting various aspects of life worldwide. The younger generation plays a vital role as agents of change in mitigating the impacts of climate change by increasing literacy and awareness of this issue. This study aims to examine the improvement of climate change literacy among young people in Muhammadiyah University of Sorong through an intervention in the form of material exposure. The research employs both quantitative and qualitative approaches with a pretest and post-test design, as well as the creation of climate action content. The intervention is conducted by providing material on climate change before the post-test is administered. Data is analyzed using the Normality Test and Hypothesis Test. The Paired Sample T – test is used as the Hypothesis Test to determine the difference in literacy levels before and after the intervention. A significant increase in students' understanding of climate change was observed, rising from 46% to 73%. The results indicate a significant improvement in climate change literacy after the intervention, demonstrating the effectiveness of this method.